2008
DOI: 10.1002/pbc.21827
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate‐associated alterations of the folate and methyl‐transfer pathway in the CSF of ALL patients with and without symptoms of neurotoxicity

Abstract: BackgroundSevere neurotoxicity has been observed after systemic high‐dose and intrathecal methotrexate (MTX) treatment. The role of biochemical MTX‐induced alterations of the folate and methyl‐transfer pathway in the development of neurotoxic symptoms is not yet fully elucidated.ProcedureMTX, 5‐methyltetrahydrofolate, calcium folinate, S‐adenosylmethionine, and S‐adenosylhomocysteine were measured in the cerebrospinal fluid (CSF) of 29 patients with acute lymphoblastic leukemia (ALL) who were treated with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 34 publications
(32 reference statements)
1
43
0
3
Order By: Relevance
“…48 Methotrexate acts on leukemic cells and also likely impacts neurons by competitively inhibiting dihydrofolate reductase, depleting folic acid, and interfering with synthesis of DNA, RNA, thymidylates, and proteins. [49][50][51][52] We also found that higher cumulative doses of glucocorticoids, which exert catabolic effects on muscle by inhibiting protein synthesis and by activating proteolysis, were associated with lower hand grip For personal use only. on May 8, 2018.…”
Section: Discussionmentioning
confidence: 67%
“…48 Methotrexate acts on leukemic cells and also likely impacts neurons by competitively inhibiting dihydrofolate reductase, depleting folic acid, and interfering with synthesis of DNA, RNA, thymidylates, and proteins. [49][50][51][52] We also found that higher cumulative doses of glucocorticoids, which exert catabolic effects on muscle by inhibiting protein synthesis and by activating proteolysis, were associated with lower hand grip For personal use only. on May 8, 2018.…”
Section: Discussionmentioning
confidence: 67%
“…It seems that intrathecal methotrexate may cause subclinical meningoencephalitis and, possibly due to antifolate action, accumulation of homocysteine, which may be alternatively metabolized to excitatory sulfur-containing amino acid, leading to the excititoxcity [17,18]. Methotrexate may also cause neurotoxicity due to its effect on serotonin, dopamine, S-adenylmethionine, and adenosine metabolism [19]. Increased oxidative stress during protocol M may reflect a depletion of the nonenzymatic antioxidant system due to the higher production of ROS in the CNS.…”
Section: Discussionmentioning
confidence: 98%
“…MTX can be used as an effective alternative to radiotherapy in children. However, MTX has a significant toxic effect on CNS, and can cause acute, sub acute or chronic neurotoxity [7]. In the current cohort, incidence of methotrexate related encephalopathy was 4.8%, and all cases developed neurotoxicity in relation to IT MTX.…”
Section: Discussionmentioning
confidence: 57%